PTU-028 First Human Series Of Magnet Assisted Capsule Endoscopy (mace) In The Upper Gi Tract Using The Novel Mirocam-navi System. (9th June 2014) - Rahman, I; Pioche, M; Shim, C; Sung, I; Saurin, J-C; Patel, P
Abstract : Introduction: Attempts in employing a simple technique of capsule endoscopy for visualisation of the upper GI tract has, thus far, been experimental, cumbersome and potentially expensive. We describe the first human series for comprehensive visualisation of the upper GI tract using the simple Intromedic MiroCam-Navi system. Our aim was to demonstrate the manoeuvrability of this magnetic capsule and evaluate its ability to completely visualise and maintain views in the upper GI tract. Methods: 26 volunteers observed a 12 hr overnight fast. 30 mins before the examination volunteers drank a preparation mixture of 20 mg of maxalon syrup with simethicone and pronase. After capsule ingestion, volunteers were allowed sips of water during the procedure. The MiroCam-Navi magnet was placed at strategic points on the body surface and rotated to hold and manoeuvre the capsule. Control was assessed by moving and holding the capsule for 1 min to visualise each of the following stations: lower oesophagus, cardia, fundus, body, incisura, antrum and pylorus and also by traversing across the stomach and through the pylorus. Total procedure time was taken from the moment of ingestion of the capsule to either reaching the duodenum, or after attempting a maximum of 10mins to traverse the pylorus. All volunteers subsequently underwent a standard upper GI endoscopy within 3 days. Results: Volunteers' median age was 38 yrs (range 26–45), median BMI 24.1 (range 19.4–38.2), median volume of water consumed 800 mls (range 200 mls–1500 mls) and median procedure time 24 min (range 12–39 min). Table 1 shows the success of clear visualisation of landmarks The capsule could be held in the lower oesophagus, cardia, fundus, body and antrum in 92%, 88%, 92%, 88% and 81% occasions respectively. The capsule could be moved from the fundus to the antrum in all cases and traverse the pylorus in 50% (n = 13). Age ≥40 was associated with successful pyloric traversing (p = 0.04). There was positive concordance for 8 out of 9 minor pathological findings with standard upper GI endoscopy. A small 4 mm submucosal lesion was missed by capsule endoscopy in the cardia of one volunteer where views were obscured. Conclusion: This is the first convincing demonstration of the potential value of MACE in the upper GI tract. There is a high degree of visualisation and control, with some improvement required for optimising fundal views and traversing the pylorus. Disclosure of Interest: None Declared.